«THE CONSCIENCE OF THE WORLD» OR «CONSPIRACY OF SILENCE»? TO THE ANNIVERSARIES OF THE EVIAN AND BERMUDA CONFERENCES - D. V. Ivanov; A. V. Krylov; V. M. Morozov; V. O. Pechatnov; S. A. Sklyarov; E. O. Shebalina (Vestnik MGIMO-Universiteta)
The article represents a complex and multifaceted analysis of different aspects related to the Evian and Bermuda conferences and is based on new scientific literature and archival documents. The aspects include such issues as prerequisites for conferences in the documents of the USSR Embassy in Poland as of 1923, historical and legal analysis of the activities and outcomes of conferences from the perspective of international legal regulation of forced population migration, the evolution of F. Roosevelt’s administration policy on the issue of Jewish immigration in the 1930s-1940s, as well as the reaction of the Jewish world to the conferences. In particular, V. Pechatnov analyzes the internal and external factors of American politics, public opinion, the personal role of President Roosevelt, the imperative of waging war against the Axis countries during the conferences. The author comes to the conclusion that Roosevelt administration and the president himself were not ardent advocates of the Holocaust victims, but they were not indifferent witnesses to the tragedy, doing for Jewish immigrants more than the governments of other Western countries. In his turn, D. Ivanov carries out a legal analysis of a number of international agreements on forced migration, adopted by states within the framework of the League of Nations, as well as the reasons for their low effectiveness. The author pays special attention to political events in Europe after Hitler coming to power. The author concludes that the unpreparedness of European states and the United States to accept ethnic Jews from German-occupied countries on their territory became one of the reasons for their mass death. S. Sklyarov proves the thesis that the Evian and Bermuda conferences demonstrated the consistency of the policies of the 32 member countries, which ultimately resulted in European Jews being the victims of Holocaust. As an example of such consistency and its earlier manifestation, which did not take into account the hopelessness of the situation of Jewish refugees, are the events of 1923 in Poland. Researcher A. Krylov presents an alternative point of view on the participation of Jewish organizations in conferences. The author refutes the widespread opinion that the leaders of Jewish organizations were not allowed to participate in the above-mentioned conferences. In fact, the Zionist movement, which took the leading positions in the Jewish communities of the world, ignored these conferences, considering them harmful because of England’s persistent refusal to abolish the White Paper of 1936, which restricted Jewish immigration to Palestine. The leaders of the Zionist movement provided assistance only to those refugees who agreed to settle in Palestine.